An introduction to global citizenship - Dower, Nigel (Edinburgh Edinburgh University Press, 2003)
In this short textbook introduction to the idea of Global Citizenship, Nigel Dower examines the arguments from ethical, social and political theory for and against the view that we are global citizens. The discussion is set in its historical context but the main emphasis is on the idea of global citizenship as a cultural process, and its application in the modern world.The book is divided into three parts - the Framework, which explores the historical context and the ethical and institutional aspects of the concept of global citizenship; Applications, covering key areas of current global concern, including the environment, aid and poverty elimination, human rights, peace, and global governance; and Theoretical Issues, which explores the arguments for and against global citizenship in more depth.
Includes bibliographical references and index.
Keywords: World citizenship